2004
DOI: 10.1128/jvi.78.6.2897-2905.2004
|View full text |Cite
|
Sign up to set email alerts
|

Nodavirus Coat Protein Imposes Dodecahedral RNA Structure Independent of Nucleotide Sequence and Length

Abstract: The nodavirus Flock house virus (FHV) has a bipartite, positive-sense RNA genome that is packaged into an icosahedral particle displaying T‫3؍‬ symmetry. The high-resolution X-ray structure of FHV has shown that 10 bp of well-ordered, double-stranded RNA are located at each of the 30 twofold axes of the virion, but it is not known which portions of the genome form these duplex regions. The regular distribution of double-stranded RNA in the interior of the virus particle indicates that large regions of the enca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
98
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(114 citation statements)
references
References 19 publications
16
98
0
Order By: Relevance
“…The complexation would not consist of continuous stretches of RNA, but rather would occur in the piecemeal fashion that we have just proposed for ss-RNA segments. 40,41 A similar mechanism has been proposed by Tihova et al,32 who suggested that base pairing between RNA segments in free solution is reversible and that there are a sufficient number of secondary structures of RNA from which to select one that is particularly wellsuited to formation of a dodecahedral cage.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…The complexation would not consist of continuous stretches of RNA, but rather would occur in the piecemeal fashion that we have just proposed for ss-RNA segments. 40,41 A similar mechanism has been proposed by Tihova et al,32 who suggested that base pairing between RNA segments in free solution is reversible and that there are a sufficient number of secondary structures of RNA from which to select one that is particularly wellsuited to formation of a dodecahedral cage.…”
Section: Resultsmentioning
confidence: 88%
“…Tihova et al 32 reported two distinct peaks in the radial density distribution of RNA in flock house virus, a close relative of PaV. This bimodal radial density distribution was also found for a viruslike construct encapsidating nonviral RNA.…”
Section: B Radial Density Profile Of Rnamentioning
confidence: 88%
See 2 more Smart Citations
“…[407][408][409] Many ss-RNA viruses compact their genomes using strongly basic flexible protein arms on the inner side of capsid proteins that provoke adsorption of flexible ss-RNA genome. [410][411][412][413] All these facts underline the importance of ES forces for DNA/RNA packaging and capsid self-assembly, producing a growing number of theoretical studies on this hot topic in the last years. [414][415][416][417][418][419] A number of theoretical [420][421][422] and computational [423][424][425][426] models exist for the capsid self-assembly.…”
Section: B Capsid Self-assembly and Shell Elasticitymentioning
confidence: 99%